Presence and absence of non‐native fish species in the Wet Tropics region, Australia. Issue 3 (3rd February 2015) - Kroon, F.; Phillips, S.; Burrows, D.; Hogan, A.
Abstract : Distributional records of non‐native fish species were identified in the Wet Tropics region, Far North Queensland, Australia, through a compilation of published records and expert knowledge. A total of 1106 records were identified comprising 346 presence and four uncertain records for at least 13 species, and 756 absence records. All current presence records consist of six species from the families Cichlidae and Poeciliidae with established self‐sustaining populations in the region, probably affecting the highly diverse native fish fauna.